A robust computational investigation on C₆₀ fullerene nanostructure as a novel sensor to detect SCNˉ - Saad M. Alshahrani; Sameer Alshehri; Amal M. Alsubaiyel; Rami M. Alzhrani; Ahmed D. Alatawi; Majed Ahmed Algarni; Maram H. Abduljabbar; Andrew Ng Kay Lup; Mohd Sani Sarjadi; Md. Lutfor Rahman; Mohammed A.S. Abourehab (King Saud University, 2022)
This study explored on the adsorption properties and electronic structure of SCNˉ via density functional theory analysis on the exterior surfaces of C₆₀ and CNTs using B3LYP functional and 6-31G** standard basis set. Then adsorption of SCNˉ through nitrogen atom on the C60 fullerene is electrostatic (₋48.02 kJ molˉ1) in comparison with the C₅₉Al fullerene that shows covalently attached to fullerene surface (₋389.10 kJ mol̄ˉ1). Our calculations demonstrate that the SCNˉ adsorption on the pristine and Al-doped single-walled CNTs are ₋173.13 and ₋334.43 kJ molˉ1, indicating that the SCNˉ can be chemically bonded on the surface of Al-doped CNTs. Moreover, the adsorption of SCNˉ on the C₆₀ surface is weaker in comparison with C₅₉B, C₅₉Al, and C₅₉Ga systems but its electronic sensitivity improved in comparison with those of C₅₉B, C₅₉Al, and C₅₉Ga fullerenes. The evaluation of adsorption energy, energy gap, and dipole moment demonstrates that the pure fullerene can be exploited in the design practice as an SCNˉ sensor and C₅₉Al can be used for SCNˉ removal applications